Education And Regulation Factors Affecting Difficulties For Indonesian Arbitral Awards To Become Final And Binding - et. al., Agus Gurlaya Kartasasmita, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Parties chose arbitration in dispute for its final and binding award. However, in Indonesia, Article 70 in Law No. 30 Year 1999 regarding Arbitration and Alternative Dispute Resolutions provides the possibility for the "losing party" in the arbitration to seek annulment of the award difficult to become final and binding. This research aims to discuss several factors affecting the intention of the "losing party" to seek annulment that made Indonesian arbitral awards difficult to become final and binding. This research was normative legal research. Data consisted of ten final supreme courts' verdicts, which totaled twenty-four courts' verdicts and ten arbitral awards. The data obtained were then analyzed using a normative qualitative approach. The research found and concluded that two significant factors made the "losing party" went for annulment. The first factor was the regulation itself, and the second factor was things beyond the law. There was a low cost for submitting annulment to the court and the "bad" culture that no one would like to lose on a case. The researcher urges the amendment of Law No.30 Year 1999 to exclude the possibility of the annulment. Intensive education shall be given to businesspeople and law-enforcer, including attorneys and judges, to remind them that arbitration awards must be respected and implemented.